1) f(x) = 2x + 4, g(x) = 4x2 + 1; Find (g ∘ f)(0).
1 answer:
Answer:
<h2>
</h2>
Step-by-step explanation:
f(x) = 2x + 4
g(x) = 4x² + 1
In order to find (g ∘ f)(0) we must first find
(g ° f )(x)
To find (g ° f )(x) substitute f(x) into g(x) that's for every x in g(x) replace it with f(x)
That's
<h3>
</h3>
We have
<h3>
</h3>
Now to find (g ∘ f)(0) substitute the value of x that's 0 into (g ∘ f)(0)
We have
<h3>
</h3>
We have the final answer as
<h3>
</h3>
Hope this helps you
You might be interested in
Answer:
Step-by-step explanation:
1x•4x•5x=180 10x=180 10/10x=180/10 X= 18
Answer:
Step-by-step explanation:
your equation shown above is set up incorrectly in order to solve this i need the right equation you must plug in each number to q to find the right solution
Answer:
angle c is 13 as it said in the question
Step-by-step explanation:
What multiplies to 25 and adds to -10 -5 and -5 (x-5)(x-5) (x-5)²